SAC3 may link nuclear protein export to cell cycle progression - Jones, Amy L. (The National Academy of Sciences, 2000)
Selective movement of proteins between the nucleus and the cytoplasm is a regulatory mechanism exploited extensively by the eukaryotic cell. We have identified the evolutionarily conserved Sac3 protein, which was implicated previously in the regulation of mitosis [Bauer, A. & Kölling, R. (1996) J. Cell Sci. 109, 1575–1583] as a novel mediator of nuclear protein export. We show that Sac3p is localized to the nuclear pore, where it interacts with nucleoporins. Loss of SAC3 function results in a block in nuclear export of a nuclear export signal-containing reporter protein. Our results also demonstrate that SAC3 interacts genetically with the nuclear protein export factors Crm1p/Xpo1p and Yrb2p. Taken together, these data indicate a link between nuclear protein export and transition through the cell cycle.